(untitled) (Faridpur Medical College Journal, 2019)
Pancytopenia is a morphological description of the peripheral blood picture irrespective of its cause & it denotes simultaneous presence of anaemia, leucopenia and thrombocytopenia. The study was done to observe the demographic profile & the clinical presentations of pancytopenic patients and to find out the aetiology of pancytopenia. This cross sectional study was carried out in Medicine ward of Rajshahi Medical College Hospital from August 2005 to July 2006. A uniform protocol was followed in all cases, to have appropriate history, physical findings & laboratory investigations. The commonest cause of pancytopenia was aplastic anaemia (48%) which was followed by hypersplenism (22%) & acute leukemia (16%). The majority cases of aplastic anaemia were idiopathic (57.69%), only 42.31% cases were due to secondary causes. The majority (94%) of patients was in the age range of 14-60 years and up to 54% was in the age group of 20-40 years. The ratio of male to female in patients of pancytopenia was 1.5:1 and 3:1 in aplastic anaemia. In secondary causes of aplastic anaemia, insecticides and viral hepatitis was found to be causative agent in 45.45% cases of each followed by pregnancy in 9.10% of cases. The common presenting complains of aplastic anaemia were generalized weakness (100%), gum bleeding (76.92%), fever (76.92%) and pallor (96.15%). Faridpur Med. Coll. J. Jul 2018;13(2): 62-65